Travelling Sociability - Pirkko Raudaskoski; Thessa Jensen (Akademisk Kvarter, 2012)
The Danish mobile library as a concrete place in a material vehicle has changed remarkably throughout the years. The modern mobile library is a place for sociability. At the stops of the library route people meet, discussing books and other materials: The bus or truck itself has changed from just being a transportation unit to a place for rest, tranquility, immersion and information. In the article mobility is defined as the possibility to move artefacts, people, and encounters to different locations, thus creating new kinds of relationships and meaning. The aim of the article is to be part of the “critical engagement in and through mobilities studies” in which “researchers are making a difference to the ways in which (im)mobilities are conceived of, in research, design and areas of public policy” (Büscher et al. 2011: 14).